Political Selection and the Qualilty of Government: Evidence from South India - Timothy Besley; Rohini Pande; Vijayendra Rao (Yale University, Economic Growth Center, 2005)
This paper uses household data from India to examine the economic and social status of village politicians, and how individual and village characteristics affect politician behavior while in office. Education increases the chances of selection to public office and reduces the odds that a politician uses political power opportunistically. In contrast, land ownership and political connections enable selection but do not affect politician opportunism. At the village level, changes in the identity of the politically dominant group alters the group allocation of resources but not politician opportunism. Improved information flows in the village, however, reduce opportunism and improve resource allocation.
Keywords: O12; H11; H42; O20; 330; Development; Political Economy; Public Provision of Private Goods; Decentralization; Kommunalpolitik; Ländliche Entwicklung; Ökonomische Theorie der Demokratie; Neue politische Ökonomie; Indien; Governance-Ansatz